On the efficient provision of public goods by means of lotteries - Jörg Franke; Wolfgang Leininger (Center for Economic Studies and ifo Institute (CESifo), 2013)
We provide a solution to the free-rider problem in the provision of a public good. To this end we define a biased indirect contribution game which provides the efficient amount of the public good in non-cooperative Nash equilibrium. No confiscatory taxes or other means of coercion are used. We rather extend the model of Morgan (2000), who used fair raffles as voluntary contribution schemes, to unfair or biased raffles, which we show to be equivalent to fair raffles whose tickets are sold to consumers at different individual prices. We give a detailed account of the solution for the case of two different consumers and discuss its implications for the general case of many consumers.
Keywords: C72; D72; H41; 330; public good provision; biased lotteries; charities